Erk signaling and chromatin remodeling in MMTV promoter activation by progestins - Vicent, Guillermo P. (The Nuclear Receptor Signaling Atlas, 2009)

(untitled)
Transcription from the mouse mammary tumor virus (MMTV) promoter can be induced by progestins. The progesterone receptor (PR) binds to a cluster of five hormone responsive elements (HREs) and activates the promoter by synergistic interactions with the ubiquitous transcription factor, nuclear factor 1 (NF1). Progesterone treatment of cells in culture leads to activation of the Src/Ras/Erk/Msk1 cascade. Selective inhibition of Erk, or its target kinase Msk1, interferes with chromatin remodeling and blocks MMTV activation. A complex of activated PR, Erk and Msk1 is recruited to promoter after 5 min of hormone treatment and phosphorylates histone H3 at serine 10. This modification promotes the displacement of HP1γ and subsequent chromatin remodeling. Progestin treatment leads to the recruitment of the BAF complex, which selectively displaces histones H2A and H2B from the nucleosome containing the HREs. The acetyltransferase PCAF is also required for induction of progesterone target genes and acetylates histone H3 at K14, an epigenetic mark, which interacts with Brg1 and Brm, anchoring the BAF complex to chromatin. In nucleosomes assembled on either MMTV or mouse rDNA promoter sequences, SWI/SNF displaces histones H2A and H2B from MMTV, but not from the rDNA nucleosome. Thus, the outcome of nucleosome remodeling by purified SWI/SNF depends on DNA sequence. The resultant H3/H4 tetramer particle is then the substrate for subsequent events in induction. Thus, initial activation of the MMTV promoter requires activation of several kinases and PCAF leading to phosphoacetylation of H3, and recruitment of BAF with subsequent removal of H2A/H2B.